Предмет: Алгебра, автор: TETRIS24

1)f(x)=-x^3+9x^2+x-1[/tex];вычислите f ` ( - 1) ;
2)f(x)= frac{1}{4}x^4- frac{1}{3}x^3+ frac{1}{2}x^2-1 вычислите f ` (3) ;
3)f(t)=0,5t^3+0,6t^2+0,8t+8; вычислите f ` (1)

Ответы

Автор ответа: NNNLLL54
0
f(x)=-x^3+9x^2+x-1; ;; f'(x)=-3x^2+18x+1; ;; f'(-1)=-20\\\f(x)= frac{1}{4}  x^4-frac{1}{3}  x^3+frac{1}{2}x^2-1; ;; f'(x)=x^3-x^2+x; ;\\ f'(3)=27-9+3=21\\\f(t)=0,5t^3+0,6t^2+0,8t+8; ;\\f'(t)=frac{3}{2}t^2+frac{6}{5}t+frac{4}{5}; ;; f'(1)=frac{15+12+8}{10}=frac{35}{10}=3,5\\oo
Похожие вопросы
Предмет: История, автор: as5g4mp69